A reappraisal of Neocalamites and Schizoneura (fossil Equisetales) based on material from the Triassic of East Antarctica - Bomfleur, Benjamin; Escapa, Ignacio Hernán; Serbet, Rudolph; Taylor, Edith L.; Taylor, Thomas N. (Alcheringa: An Australasian Journal of Palaeontology)
Sphenophytes are a common floral element in the Triassic of Gondwana. Most sphenophyte compression fossils have been conventionally assigned to a few, presumably very widespread species of Neocalamites based on vegetative features of the stems (or pith casts) and the foliage. During recent decades, however, new reports on morphological and anatomical details of some of these fossils have cast doubt on the systematic affinities of many Gondwanan Triassic sphenophytes. Here we describe Neocalamites suberosus (Artabe & Zamuner) nov. comb. et emend. and Schizoneura africana Feistmantel emend. from several Triassic deposits in the central Transantarctic Mountains and Victoria Land, East Antarctica. The material enables a critical reevaluation of morphological and anatomical features that have been historically used to define the two genera, including leaf- base morphology, degree of leaf fusion, stem vasculature and vallecular canals, and features of the nodal diaphragm. The diagnoses of Neocalamites and Schizoneura are emended so that they more accurately reflect recent advances in our understanding of the anatomy and ontogeny of these plants. Fil: Bomfleur, Benjamin. University of Kansas; Estados Unidos de América; Fil: Escapa, Ignacio Hernán. Museo Paleontologico Egidio Feruglio; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Serbet, Rudolph. University of Kansas; Argentina Fil: Taylor, Edith L. University of Kansas; Estados Unidos de América; Fil: Taylor, Thomas N. University of Kansas; Estados Unidos de América;